Five-year single-centre experience of carcinoma of the oesophagus from Blantyre, Malawi - Chetwood, John David (BMJ Open Gastroenterol, 2018)
BACKGROUND: Oesophageal squamous cell carcinoma (OSCC) is increasing worldwide and has an exceptionally high prevalence in certain distinct geographical locations such as the African oesophageal SCC corridor. Despite this, there is a paucity of evidence to characterise the disease particularly in the Malawian context. METHOD: We retrospectively audited our endoscopy database over 5 years, including for patient demographics, endoscopy findings, therapeutic intervention and recommendations for treatment. RESULTS: 1586 patients with oesophageal cancer were identified from a total of 5882 endoscopy records from 2013 to 2017. Our cohort showed a larger proportion of oesophageal cancers found higher in the oesophagus compared with other African studies and a female preponderance in this upper-oesophagus disease subset though a male preponderance overall. 39% of patients with oesophageal cancer underwent bougie dilatation and 11% underwent palliative stent placement, which likely reflects local availability of resources. CONCLUSION: This study validates the observation that OSCC predominates in sub-Saharan Africa in Malawi over other forms of oesophageal carcinoma, though our cohort appears to have subtly distinct demographics and disease-specific data. This highlights the need to prioritise preventative and therapeutic strategies for OSCC in this and similar settings.